COMBUSTION and PYROLYSIS of A SLUDGE FROM WASTEWATER TREATMENT PLANT - Morais, L. C. [UNESP]; Dweck, J.; Campos, V. [UNESP]; Rosa, André Henrique [UNESP]; Fraceto, L. F. [UNESP]; Buechler, P. M. (Trans Tech Publications Ltd, 2010)
The possibility of thermal treatment plants of municipal wastewater is an alternative solution for the final disposition of the sludge produced on small cities as Barueri, a small town of São Paulo State, Brazil. Combustion and pyrolysis of that municipal waste, occurring respectively in air and nitrogen, have been studied by thermogravimetry (TG) and differential thermal analysis (DTA). The main steps of each case were analyzed and Kissinger plots were used to estimate respective activation energies. DTG peaks are more indicated to represent the condition of maximum reaction rates than DTA peaks.
Keywords: Sludge; pyrolysis; combustion; activation energy